The outcome of relapsed and residual clubfeet treated with the Taylor Spatial Frame - Botha, Adriaan Hendrik; Du Toit, Jacques; Lamberts, Robert P. (Stellenbosch : Stellenbosch University, 2015)
Thesis (MMed)--Stellenbosch University, 2014.